Ijtihad Jama’i (Ijtihad Kolektif) Perspektif Ulama Kontemporer - Faishal Agil Al Munawar; Mirwan (Program Pascasarjana Universitas Ibrahimy, 2020)
The research discusses Ijtihad Jama’i or more familiar known as Collective Ijtihad. It uses Library Research with a descriptive comparative study approach which explains the definition of Collective Ijtihad, the importance and its position under Islamic Law according to contemporary Islamic scholars. The results have shown that Collective Ijtihad is an agreed Islamic law (fiqh) mechanism upon respectable Islamic scholars (mujtahid) to generate law verdict from recent thematic issues. The earliest step analyzes previous law verdicts from similar cases based on prior Islamic scholars’ notions. The latter work comes into the judgment selection process to produce a decree with most robust yet relevant from available references. Currently, Collective Ijtihad has high gravity in the making of pure tasyri’ (Islamic Law), stationed under original Ijma’ but superior to Qiyas and all Individual Ijtihad yet should be applied as Islamic Law determination method (istinbath) due to relaxed prerequisites and straightforward implementation compare to Individual Ijtihad, which is very influential in deciding contemporary Islamic Legislation